2021
DOI: 10.1180/mgm.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

Gold particle geomicrobiology: Using viable bacteria as a model for understanding microbe–mineral interactions

Abstract: This is a 'preproof' accepted article for Mineralogical Magazine. This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Some researchers have suggested that seafloor manganese nodules form, at least in part, through such biochemical processes (Lysyuk 2008;Blöthe et al 2015). Microbes have also been invoked in the precipitation of gold (Au; Reith et al 2006Reith et al , 2009Johnston et al 2013;Sanyal and Shuster 2021), copper carbonate (Li and Gadd 2017) (Carpentier et al 2003), and polymorphs of sulfur (Douglas and Yang 2002;Gleeson et al 2011;Cron et al 2019).…”
Section: Stage 10a Neoproterozoic Oxygenation and The Phanerozoic Biosphere The Phanerozoicmentioning
confidence: 99%
“…Some researchers have suggested that seafloor manganese nodules form, at least in part, through such biochemical processes (Lysyuk 2008;Blöthe et al 2015). Microbes have also been invoked in the precipitation of gold (Au; Reith et al 2006Reith et al , 2009Johnston et al 2013;Sanyal and Shuster 2021), copper carbonate (Li and Gadd 2017) (Carpentier et al 2003), and polymorphs of sulfur (Douglas and Yang 2002;Gleeson et al 2011;Cron et al 2019).…”
Section: Stage 10a Neoproterozoic Oxygenation and The Phanerozoic Biosphere The Phanerozoicmentioning
confidence: 99%